2020
DOI: 10.1016/j.jcot.2020.02.007
|View full text |Cite|
|
Sign up to set email alerts
|

Is it necessary to tie the medial row in rotator cuff repair double-row constructs when using suture tape?

Abstract: To evaluate the selected biomechanical differences of a double-row trans-osseous equivalent rotator cuff repair with a knotless versus knot-tying medial row using suture tape in regard to repair displacement, stiffness, and ultimate load to failure. Methods: In 16 fresh-frozen human shoulders (8 matched pairs), double-row rotator cuff repairs were performed with medial-row mattress knots (MK) on one side, the other without (NK). Two DVRT (Differential Variable Reluctance Transducer) sensors were attached betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…26,29,30 A recent biomechanical study by Mijares et al showed no significant difference between a knotted or knotless TOE using suture tape in medial row fixation point displacement, construct stiffness or load to failure in human cadaveric shoulders. 31 In our study there was a significant decrease in symptomatic re-tear rate in patients that had a suture tape RCR with a knotted medial row, with this group being 82% less likely to experience a re-tear.…”
Section: Discussionsupporting
confidence: 44%
“…26,29,30 A recent biomechanical study by Mijares et al showed no significant difference between a knotted or knotless TOE using suture tape in medial row fixation point displacement, construct stiffness or load to failure in human cadaveric shoulders. 31 In our study there was a significant decrease in symptomatic re-tear rate in patients that had a suture tape RCR with a knotted medial row, with this group being 82% less likely to experience a re-tear.…”
Section: Discussionsupporting
confidence: 44%
“… 16 , 18 , 22 , 23 , 24 , 25 , 26 Conversely, Mijares et al. 27 showed that no significant differences exist regarding displacement across the repair site, stiffness, and ultimate load to failure. Other studies have shown that even if present, biomechanical advantages may come at the expense of heightened strain at the medial suture level where the knots are tied.…”
mentioning
confidence: 98%
“…Multiple laboratory studies showed no significant difference in contact pressures between untied and tied medial row. 14 , 15 However, we have observed increased gap formation on the articular side in knotless medial-row constructs, which is an unfavorable condition in tendon repairs. Gapping at the repair site also allows synovial fluid leakage to the footprint, which was previously proposed to be an unfavorable environment for tendon healing.…”
Section: Discussionmentioning
confidence: 90%